Learning in the Digital Age Full of Hedonistic Cultural Values Among Elementary School Students - Aslan, Aslan; Shiong, Pong Kok (Bulletin of Pedagogical Research, 2023)
The era of digital development that dominates the world with the sophistication of today's internet networks, especially the impact of the COVID-19 pandemic, has created a learning system using mobile phones with internet networks. On the one hand, there are negative and positive impacts. The article aims to analyze earning in the Digital Age Full of Hedonistic Cultural Values Among Elementary School Students. This research method is qualitative with a literature review approach. From the collected literature, this study shows negative values with hedonistic behavior, which then becomes a habit that has a negative impact. It was inseparable from the cell phones used by children as learning media. Still, at that time, parental control was not maximal over cell phone features, which became a consumptive spectacle that impacted children's behavior. Therefore, this new insight becomes a new idea to support similar research in the future. Keywords: Digital Development, Hedonistic Culture Values, Learning in Digital Age